Initial field performance of a hybrid CPV‐T microconcentrator system. (25th May 2012) - Vivar, M.; Everett, V.; Fuentes, M.; Blakers, A.; Tanner, A.; Le Lievre, P.; Greaves, M.
ABSTRACT The first prototype of the hybrid CPV‐T ANU‐Chromasun micro‐concentrator has been installed at The Australian National University, Canberra, Australia. The results of electrical and thermal performance of the micro‐concentrator system, including instantaneous and full‐day monitoring, show that the combined efficiency of the system can exceed 70%. Over the span of a day, the average electrical efficiency was 8% and the average thermal efficiency was 50%. Copyright © 2012 John Wiley & Sons, Ltd.